Climate security mapping for targeted WFP humanitarian interventions in the Liptako-Gourma region. Climate security hotspots and food security insights - Sarzana, Carolina; Ouedraogo, Yacouba; Renkamp, Theresa; Doehnert, Federico; Cissé, Amadou; Sib, Ollo; Kenduiywo, Benson; Korir, Victor; Läderach, Peter (2024)
The Liptako Gourma region, encompassing Mali, Niger, and Burkina Faso, faces a crisis where climate change, conflict, and food insecurity intersect. Rising temperatures, erratic rainfall, and prolonged droughts are disrupting agriculture and intensifying resource competition, fueling local conflicts. In these transboudary provinces, non-state armed groups exploit resource-related grievances to expand their influence, worsening food insecurity, especially in agricultural and livestock-dependent communities.